Flowering Plants. Eudicots Apiales, Gentianales (except Rubiaceae) (The Families and Genera of Vascular Plants ;, 2018)
This volume covers the orders Apiales (Asterids I) and Gentianales (except Rubiaceae; Asterids II). It is the last of five volumes to (almost) complete the treatment of the Asterids in this series after publication of Vols. VI (Cornales, Ericales, 2004), VII (Lamiales, 2004), VIII (Asterales, 2007) and XIV (Aquifoliales, Boraginales, Bruniales, Dipsacales, Escalloniales, Garryales, Paracryphiales, Solanales, Icacinaceae, Metteniusaceae, Vahliaceae, 2016). The present volume provides descriptions for 11 families with altogether 1021 genera. Identification keys are provided for families within orders and for all genera within families, and likely phylogenetic relationships are discussed. The wealth of information contained in this volume makes it an indispensable source for all working in pure and applied plant sciences.